YouTube as a source of information on sacroiliac joint injection: A reliability and quality analysis - ÖZTÜRK, EKİM CAN; SAÇAKLIDIR, REKİB; ŞENCAN, SAVAŞ; GÜNDÜZ, OSMAN HAKAN (My University, 2023)
Sacroiliac joint (SIJ) injection is recommended for both diagnosis and relief of SIJ pain. YouTube has become a widely used source for health professionals and patients to obtain information about various procedures but the quality of YouTube videos including medical content is questionable. Therefore, the aim of this study is to evaluate the quality of SIJ injection videos on YouTube. This cross-sectional study was conducted through March 2022 by searching the phrase \"sacroiliac joint injection\"on YouTube. After resetting search history top 100 videos were screened. Duration of videos, number of views, number of likes, number of comments, view ratio (number of views/d), time passed since upload date, guide used for injection, and source of videos were recorded. The DISCERN and the Global Quality Scale were used to assess the quality and reliability of the videos. Of the 100 videos screened 42 videos met the inclusion criteria. The videos (73.8%) were predominantly uploaded by physicians. Most frequently used guide for injections was ultrasound with 45.4%. According to the DISCERN classification, 35.7% of the videos were \"very poor,\"30.9% were \"poor,\"21.4% were \"fair,\"7.1% were \"good\"and 4.7% were \"excellent.\"Physicians and patients should be aware of that many of the videos about SIJ injections are categorized as \"poor\"or \"very poor,\"which means they may mislead trainees, resulting in inadequate treatments.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; quality; sacroiliac joint injection; video; YouTube; quality; sacroiliac joint injection; video; YouTube